1994
DOI: 10.1128/mcb.14.1.492
|View full text |Cite
|
Sign up to set email alerts
|

Efficient coupling with phosphatidylinositol 3-kinase, but not phospholipase C gamma or GTPase-activating protein, distinguishes ErbB-3 signaling from that of other ErbB/EGFR family members.

Abstract: Recombinant expression of a chimeric EGFR/ErbB-3 receptor in NIH 3T3 fibroblasts allowed us to investigate cytoplasmic events associated with ErbB-3 signal transduction upon ligand activation. An EGFR/ErbB-3 chimera was expressed on the surface of NIH 3T3 transfectants as two classes of receptors possessing epidermal growth factor (EGF) binding affinities comparable to those of the wild-type EGF receptor (EGFR). EGF induced autophosphorylation in vivo of the chimeric receptor and DNA synthesis of EGFRI ErbB-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
180
0
3

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(189 citation statements)
references
References 66 publications
6
180
0
3
Order By: Relevance
“…Indeed, high concentrations of c-erbB3/c-erbB4 ligands, may even result in a parallel inhibition of cellular proliferation (Bacus et al, 1992;Grunt et al, 1995). Although there is clearly substantial overlap of the expression of individual erbB family members within the breast cancer population, the di erential e ects of c-erbB3/cerbB4 and the EGFR may result from the ability of cerbB3 to e ciently recruit PI3 Kinase (Solto et al, 1994;Fedi et al, 1994;Prigent and Gullick, 1994) and hence pro®ciently activate additional signal transduction pathways to those employed by EGFR. Relative availabilities of ligands, receptors and secondary pathways would appear to critically alter the proliferation/di erentiation status of breast tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, high concentrations of c-erbB3/c-erbB4 ligands, may even result in a parallel inhibition of cellular proliferation (Bacus et al, 1992;Grunt et al, 1995). Although there is clearly substantial overlap of the expression of individual erbB family members within the breast cancer population, the di erential e ects of c-erbB3/cerbB4 and the EGFR may result from the ability of cerbB3 to e ciently recruit PI3 Kinase (Solto et al, 1994;Fedi et al, 1994;Prigent and Gullick, 1994) and hence pro®ciently activate additional signal transduction pathways to those employed by EGFR. Relative availabilities of ligands, receptors and secondary pathways would appear to critically alter the proliferation/di erentiation status of breast tumours.…”
Section: Discussionmentioning
confidence: 99%
“…However, the phosphotyrosine content of ErbB3 decreased in parallel with the loss of ErbB2 from the plasma membrane ( Figure 2b, lower panel). Compared with the other ErbB receptors, the cytoplasmic tail of ErbB3 contains more potential docking sites for the p85 subunit of PI3K (Fedi et al, 1994;Prigent and Gullick, 1994), allowing it to couple e ciently to this kinase . A GST pull-down assay using the SH2 domain of p85, showed that signi®cantly less ErbB3 was precipitated after 72 h scFv-5R induction ( Figure 2c, lane 3).…”
Section: Erbb2 Down-regulation Affects Erbb3 Activitymentioning
confidence: 99%
“…These transfectants have previously been characterized and are known to express individual ErbB receptors in the range of 0.6 ± 3610 6 molecules/cell (Di Fiore et al, 1987b;Kraus et al, 1993;Fedi et al, 1994;. A recombinant model system expressing high receptor levels was utilized, to facilitate sensitive and speci®c detection of single ErbB family members, as frequent co-expression of ErbB receptors in human tumor cell lines may confound de®nition of a receptorspeci®c response.…”
Section: Recombinant Antigen Sources For Human Erbb Receptorsmentioning
confidence: 99%
“…A recombinant model system expressing high receptor levels was utilized, to facilitate sensitive and speci®c detection of single ErbB family members, as frequent co-expression of ErbB receptors in human tumor cell lines may confound de®nition of a receptorspeci®c response. Figure 1 illustrates detection of EGFR, ErbB2, ErbB3 or ErbB4 in the 170-185 kDa region of the corresponding transfectant by receptorspeci®c polyclonal rabbit antisera raised against carboxyl-terminal epitopes of single ErbB receptors (Fedi et al, 1994;Alimandi et al, 1995;Kraus et al, 1993;Baulida et al, 1996). Overexpression of the respective recombinant human ErbB receptor was validated in LTR-EGFR, LTR-ErbB2, LTR-ErbB3, or LTR-ErbB4 when compared with NIH3T3 controls (Figure 1).…”
Section: Recombinant Antigen Sources For Human Erbb Receptorsmentioning
confidence: 99%
See 1 more Smart Citation